PEMBELAJARAN BIOLOGI BERORIENTASI LIFE SKILL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SMA KARTIKATAMA METRO - Muhfahroyin Muhfahroyin (Bioedukasi Jurnal Pendidikan Biologi, 2010)
The objective of this research are to increase the student activities and  learning  achievement in Biology Learning. This Research conducted using Classroom Action Research two cycles. The result of this research shows that life skills oriented biology learning contributed the increase of students’ activities and their learning achievement. It can be seen from  the increase of students’ learning activities from 67,5% in cycle I  to  91% cycle II.  Contextual Teaching and Learning (CTL) approach also able to increase the student achievements. In cycle I, the average score of student is 70,53 increasing to 79,83.  From this research, the researcher suggest that Contextual Teaching and Learning (CTL) approach should be applied, especially to integrate the values of IMTAQ in Biology learning and other subject